PENGEMBANGAN MODUL EDUKASI ANAK NAKAL - Khairunnisa, Khairunnisa; Yakub, Elni; Saam, Zulfan (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The module is an independent learning package which includes a series of planned learning experiences and is systematically designed to help students achieve learning goals. With module teaching materials, students are able to study independently without or with the guidance of the teacher, there is control over student learning outcomes through the competency standards in each module, as well as being more responsible for their actions. The purpose of this research is to find out the procedure of developing a naughty child education module and to find out the results of the validation of a naughty child education module. The implementation of educational development procedures has passed through six stages, namely; 1) Potential and problems; 2) Collection of data or information; 3) Product design; 4) Design validation; 5) Design revisions; 6) Product manufacture. After going through the stages of study and analysis and revision, the results of the validity of the education module for gadget addictions indicate that the assessment after on average then get a value of 80.50%, overall the module is eligible to be used as teaching material, especially in the field of guidance and counseling. This feasibility is supported by the results of evaluations by several experts.Key Words: Module, Education, Naughty Children